A Low Cost, Large Bandwidth Patch Antenna design for utilization in Frequency Diverse Arrays - Iqbal, Usama Mozammil (2023)
A Master of Science thesis in Electrical Engineering by Usama Mozammil Iqbal entitled, “A Low Cost, Large Bandwidth Patch Antenna design for utilization in Frequency Diverse Arrays”, submitted in June 2023. Thesis advisor is Dr. Lutfi Albasha and thesis co-advisor is Dr. Hasan Mir. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).